Effect of microfiber diameters on micro-sphere resonator based humidity sensor / Ummu Umairah Mohamad Ali ...[et al.] - Mohamad Ali, Ummu Umairah; Jusoh, Zulzilawati; Md Johari, Md Ashadi; Abdul Rahman, Husna; Adnan Zain, Huda; Zulkipli, Nur Farhanah; Harun, Sulaiman Wadi (UiTM Press, 2022)
In this paper, the effect of microfibers diameter on the micro-sphere resonators (MSR) ability to detect relative humidity changes is analyzed. Microspheres show whispering gallery mode (WGM) characteristics when light is properly coupled into them. The interaction between that coupled light and the surroundings can be used for sensing applications. Three different diameters of microfiber were used to couple light into the MSR, 5 μm, 8 μm and 10 μm. The MSR with the sphere diameter of 200 μm was categorized by its quality factor and spectrum transmission modes. Then, the structure was used as a humidity sensor. The transmission modes of the MSR were compared at three different tapering sizes. Each of these structures was tested as a humidity sensor in the relative humidity range 50-90%. In addition, sensitivity, and linearity of the three proposed sensors were calculated. According to the compared results, the 5 μm microfiber has a much better sensitivity than the 8 μm and 10 μm microfiber when using the MSR.